APPLICATIONS OF DOPPLER ULTRASOUND IN ASSESSING FETAL WELL-BEING - NAZ , A; YASEEN , MM; SOOMRO , NA; SHAIKH , H; TASNEEM , M; HAMEED , L; AAMIR , K; RAMZAN , A (Biological and Clinical Sciences Research Journal, 2023)
The study aimed to determine the frequency of Doppler velocimetry usage in high-risk pregnancies and to compare the results between patients who received Doppler velocimetry and those who did not manage high-risk pregnancies. This descriptive study was conducted between January 2022 and December 2022 in the Gynaecology and Obstetrics Department of PUMHS Nawabshah. A total of 110 pregnant women were admitted to the Department of Obstetrics and Gynecology’s OPD and ER. Both the patient and their guardian signed an informed consent form. Fifty-five patients underwent Doppler ultrasound in group I, while 55 patients did not have Doppler ultrasound in group II. A blood sample was obtained from each patient for baseline tests such as complete blood count, electrolytes, blood sugar level, blood urea, serum creatinine, and others. All data was analyzed using SPSS 26.0. The patient’s mean age in group I was 26.12±6.39 years with a body mass index of 25.7±5.24 kg/m2, and in group II, the mean age was 27.4±10.67 years with a body mass index of 26.13±5.57 kg/m2. Gestational age in group I was 37.15±8.38 weeks, and in group II was 36.9±7.43 weeks. Frequency of C-section in group I was found in 30 (54.5%) and in group II was in 41 (74.5%) cases with p <0.004. Preterm deliveries were higher in group II in 26 (47.3%) cases than in group I in 15 (27.3%) cases. Abnormal amniotic fluid was higher in group I in 27 (49.1%) cases than in group II in 20 (36.4%). Doppler studies played a significant role in managing high-risk pregnancies and improving perinatal and neonatal outcomes. However, using other fetal well-being tests already well-established in clinical practice at each institution affects the role of Doppler studies in late pregnancy.